2018
DOI: 10.1111/codi.14102
|View full text |Cite
|
Sign up to set email alerts
|

Patients with perianal Crohn's fistulas experience delays in accessing anti‐TNF therapy due to slow recognition, diagnosis and integration of specialist services: lessons learned from three referral centres

Abstract: This study highlights two key challenges in the treatment pathway: (i) delays in diagnosis of underlying CD in patients with anal fistula and (ii) the pathway to anti-TNF therapy is long, suggesting issues with service design and delivery. These should be addressed to improve patient experience and outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…We believe that OE could be an efficacious answer to the issues recently underlined by Lee et al [15] and those reported above. OE can be a part of a clinical pathway for patients with perianal Crohn's fistulas.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…We believe that OE could be an efficacious answer to the issues recently underlined by Lee et al [15] and those reported above. OE can be a part of a clinical pathway for patients with perianal Crohn's fistulas.…”
Section: Discussionmentioning
confidence: 59%
“…[13,14]. Early diagnosis and correct treatment are crucial to allow patients to promptly start medical treatments with antitumor necrosis factor (tnf) which is considered the cornerstone of treatment, offering the best long-term control of PAD [15,16]. The diagnosis and treatment may be delayed since the clinical pathway for this subset of patients is still not fully standardized, even in specialized centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptomatic anal fistula in patients with Crohn’s disease (CD) requires proper and timely treatment in order to avoid perianal sepsis and allow prompt initiation of anti‐TNF‐alpha treatment [1]. Guidelines and clinical recommendations specific for this period of global crisis for inflammatory bowel disease (IBD) suggest that IBD is treated as usual and recommend that any therapy should be administered while minimizing exposure of people and potential transmission [2].…”
mentioning
confidence: 99%
“…Management of patients with fistulating perianal Crohn's disease is especially complex as optimal therapy involves surgical stabilization of disease with drainage and seton insertion followed by biological therapy . We have shown that the median time from presentation of symptoms to initiation of biological therapy is 7 months in three major UK teaching hospitals and 25% of patients wait longer than 18 months even when the diagnosis of Crohn's disease is known .…”
mentioning
confidence: 99%